The impact of tax-benefit systems on low-income households in the Benelux countries: A simulation approach using synthetic datasets - Frédéric Berger; Monique Borsenberger; Herwig Immervoll; Julie Lumen; Bertrand Scholtus; Klaas De Vos (University of Essex, Institute for Social and Economic Research (ISER), 2001)
Computing the tax-benefit position of similar typical households across countries is a method widely used in comparative fiscal- and social policy research. These calculations provide convenient summary pictures of certain aspects of tax-benefit systems. They can, however, be seriously misleading because they reduce very complex systems to single point estimates. Using an integrated European tax-benefit model (EUROMOD), we substitute the typical household by a synthetic dataset, which can be used across countries. By varying certain important household characteristics (notably income), this dataset captures a much larger range of household situations. The calculations performed on this range of households not only show the tax-benefit position of many individual households but also demonstrate which household characteristics determine taxes and benefits in each country. Hypothetical calculations such as those presented here do not exploit the ability of EUROMOD to determine the impact of social and fiscal policies on actual populations. Nevertheless, they can be a valuable contribution to understanding tax-benefit systems since they allow us to separate the effects of tax-benefit rules from those of the population structure. We compute and compare disposable incomes for a large range of pre-tax-and-benefit income (so called budget constraints) of households in the Benelux countries. Disposable incomes are then decomposed to separately show the effects of each simulated tax and transfer payment. Based on these results, we illustrate the performance of the three tax-benefit systems in terms of ensuring a minimum level of household income.
Keywords: 330; Microsimulation; European Union; Benelux; Average Production Worker; Poverty; Steuerbegünstigung; Niedrigeinkommen; Simulation; Benelux-Staaten